Attitude of the Youth Towards the Elderly People in the Selected Community in Lalitpur District of Nepal - Gaire, Bipula; Khagi, Bina Rana (Med Phoenix, 2020)
Introduction: Global ageing is the success story of the 21st century as a result of declining fertility, mortality and improved public health interventions. With the increased elderly population, the attitude of societies about ageing changes. Positive attitudes towards the elderly people are valued, respected and experienced but most of the literature shows negative perceptions towards elderly people among the youth, especially in the form of stereotypical behaviors and ageism which can result in social exclusion, isolation and ultimately the abuse of elderly people and disempowerment of elderly people. Methods: Cross sectional research design was used to assess the attitude of youth towards the elderly people in the selected community of Lalitpur, Nepal from August 12 to September 7, 2018. Total 380 youth were interviewed by using modified Kogan’s Old People Scale and structured questions. Systematic random sampling technique was used for data collection. Results: More than half of the youth (66.1%) had positive attitude level towards the elderly. With regards to the attitude towards the care of elderly almost of all of the youth (97.9%) had positive attitude towards the care of the elderly. There was significant association between gender and attitude towards elderly (p=0.04) and occupation and attitude towards the care of the elderly (p=0.02) at 95% of significance level. Conclusion: Although more than half of the youth have positive attitude toward the elderly people still there is need to provide awareness program regarding the physical, physiological and psychological changes that occurs during the ageing period which helps in enhancing the positive attitude of the youth and thus contributing towards overall quality of life of the elderly people.